UPAYA MENINGKATKAN DISIPLIN GURU MELALUI PEMBERIAN REWARD DAN PUNISHMENT DI SDN 3 WONOHARJO TAHUN AJARAN 2018/2019 - Suryamah Anshori (Wahana Pendidikan, 2020)
ABSTRACTThis study aims to improve teachers' discipline in SDN 3 Wonoharjo, Indonesia. The study was conducted through two cycles, each cycle through the stages of planning, implementing actions, observation and reflection. The method used for the data collection was observation and documentation. Based on the data analysis, approximately 1 month, with the concept of 2 times, the implementation of reward and punishment programs has a positive impact on the process of increasing teachers’ discipline. Reward and punishment programs are very suitable for teachers. The efforts to improve teachers’ discipline through the provision of rewards and punishments by the Principal was on target. The results of the first 10 days were in a score of 115. This has fulfilled the expectation score of 101. The results of the reflection of the implementation of the other 10 days were in a score of 133. It proved that the teachers’ discipline was very good because it approached the maximum score. The results of the questionnaire showed that the score obtained in the first 10 days was 154 which is still far from the maximum score but the teacher had shown changes to be better in terms of their discipline. The results of the questionnaire in the second 10 days showed a very good score of 214 with a maximum score of 240. This showed that the teacher's discipline was very good. Keywords: Teacher Discipline, Reward, Punishment. ABSTRAKPenelitian ini bertujuan meningkatkan disiplin guru di SDN 3 Wonoharjo. Penelitian dilaksanakan melalui dua siklus yang masing-masing siklus melalui tahapan perencanaan, pelaksanaan tindakan, observasi dan refleksi. Metode yang digunakan untuk pengumpulan data adalah metode observasi dan metode dokumen. Berdasarkan analisis data, dalam jangka waktu kurang lebih 1 bulan, dengan konsep 2 kali pelaksaan program pemberian reward dan punishment memiliki dampak positif bagi proses peningkatan kedisiplinan Guru pada proses mengajar. Program pemberian reward dan punishment sangat cocok di terapkan pada guru. Upaya meningkatkan kedisiplinan Guru pada proses mengajar melalui pemberian reward dan punishment oleh Kepala Sekolah tepat sasaran. Hasil dari refleksi pelaksanaan 10 hari pertama ini mengahasilkan skor 115. Hal tersebut sudah memenuhi skor harapan yaitu 101. Hasil refleksi pelaksanaan 10 hari ke 2 ini mengahasilkan skor 133 artinya kedisiplinan guru sudah sangat baik karena mendekati skor maksimal. Adapun hasil angket menunjukkan skor yang di dapat pada 10 hari pertama adalah 154 masih jauh dari skor maksimal namun guru sudah menunjukkan perubahan ke lebih baik dalam hal kedisiplinan. Hasil angket menunjukkan skor yang sangat bagus yakni 214 dengan skor maksimal 240. Hal ini berarti bahwa kedisiplinan guru sudah sangat baik. Kata Kunci: Disiplin Guru, Reward, Punishment.